Incomplete Question
The value of x'(π/2) is not given.
I'll assume x'(π/2) to be 1
Answer:
x(t) = cos(t)
Step-by-step explanation:
Given
x(t) = c1 cos(t) + c2 sin(t)
x(π/2) = 0
x'(π/2) = 1
First, we'll differentiate x(t) to give x'(t)
x'(t) = - c1 sin(t) + c2 cos(t)
Given that x(π/2) = 0
We substitute π/2 for t in x(t)
So,
x(t) = c1 cos(t) + c2 sin(t) becomes
c1 cos(π/2) + c2 sin(π/2) = 0
cos (π/2) = 0 and sin(π/2) = 1;
So, we have
c1 * 0 + c2 * 1 = 0
0 + c2 = 0
c2 = 0.
Given that x'(π/2) = 1
We substitute π/2 for t in x'(t).
So,
x'(t) = - c1 sin(t) + c2 cos(t) becomes
-c1 * sin(π/2) + c2 * cos(π/2) = 1
-c1 * 1 + c2 * 0 = 1
-c1 =+ 0 = 1
-c1 = 1
c1 = 1.
So,
x(t) = c1 cos(t) + c2 sin(t)
=>
x(t) = 1 * cos(t) + 0 * sin(t)
x(t) = cos(t)